Interleukin-6 (IL-6) dan Jalur NF-ΚB Target Kunci Inflamasi dalam Proses Penuaan - Dewi, Ade Yasinta; Dewi, Ni Nyoman Ayu (Syntax Literate, 2025)
Aging is a complex biological process characterized by a gradual decline in physiological functions and increased susceptibility to degenerative diseases. A hallmark of aging is low-grade, chronic, non-infectious inflammation known as inflammaging. This phenomenon is driven by the accumulation of senescent cells that actively secrete pro-inflammatory mediators through the senescence-associated secretory phenotype (SASP). Among these mediators, Interleukin-6 (IL-6) and the transcription factor Nuclear Factor-kappa B (NF-κB) play central roles. NF-κB acts as a master regulator of pro-inflammatory gene expression, including IL-6, and is activated by various stimuli such as oxidative stress and DNA damage. IL-6 secreted by senescent cells activates the JAK/STAT3 pathway, which in turn enhances NF-κB activity, creating a positive feedback loop that sustains chronic inflammation. This mutual reinforcement between IL-6/STAT3 and NF-κB signaling drives progressive tissue damage, impairs regeneration, and increases the risk of age-related diseases such as atherosclerosis, diabetes, osteoarthritis, and neurodegenerative disorders. This review discusses the roles of IL-6 and NF-κB in the mechanisms of inflammaging and evaluates their potential as therapeutic targets to slow aging and prevent age-associated diseases.